PENGARUH KOMPENSASI, ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN WORK LIFE BALANCE TERHADAP KINERJA KARYAWAN PT KARYA GAGAS MULIA DI SUMENEP - Hanilyana, Devi; Abrar, Unsul (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
Employee performance is one of the key elements in determining the success of an organization. This study aims to determine the effect of compensation, Organizational Citizenship Behavior and Work Life Balance on employee performance at PT Karya Gagas Mulia, Sumenep. The method used is a quantitative approach, with the study population covering all employees of the company. The sampling technique was carried out by probability sampling using the random sampling method, obtaining 57 respondent samples. For data collection, a Likert scale-based questionnaire was used, which measured respondents' perceptions of the influence of well-being, organizational citizenship behavior, and work-life balance on their performance. Data processing was carried out using SPSS software version 26. The results of the analysis showed that partially, the three independent variables (compensation, OCB, and WLB) had a positive and significant effect on employee performance. While simultaneously, the three variables contributed greatly to improving performance, as seen from the R Square value of 0.819 or 81.9%. This means that most of the variables in employee performance can be explained by these three factors, while the remaining 18.1% is influenced by other variables not discussed in this study